2021
DOI: 10.3389/fped.2021.645511
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrent Tracheoesophageal Fistula After Gross Type C Esophageal Atresia Repair

Abstract: Background: To determine the possible risk factors of recurrent tracheoesophageal fistula (rTEF) after Gross type C esophageal atresia (EA) and tracheoesophageal fistula (TEF) repair.Methods: The medical records of 343 pediatric patients with Gross type C EA/TEF who underwent surgical repair were retrospectively analyzed. The patients were retrospectively divided into two groups according to whether they had rTEF. Univariate and multivariable logistic regression analysis were performed to identify risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…[6] Patients with recurrent TEF present with non-resolving cough, choking and apnea during feeds, recurrent pneumonia and if neglected may result in chronic lung disease. [1,5,6,7] The age at presentation has been reported as 3 weeks to 32 years. [5,6] Recurrent TEF after primary repair of EA with distal TEF has been found as a sequela of mediastinal abscess because of leaked anastomosis or esophageal perforation after forceful dilatation of anastomotic stricture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6] Patients with recurrent TEF present with non-resolving cough, choking and apnea during feeds, recurrent pneumonia and if neglected may result in chronic lung disease. [1,5,6,7] The age at presentation has been reported as 3 weeks to 32 years. [5,6] Recurrent TEF after primary repair of EA with distal TEF has been found as a sequela of mediastinal abscess because of leaked anastomosis or esophageal perforation after forceful dilatation of anastomotic stricture.…”
Section: Discussionmentioning
confidence: 99%
“…[5,8] Some studies have also shown an association between premature birth, low birth weight, anastomotic stricture, and esophageal dilatation with recurrent TEF. [1] Long-gap atresia, usage of ligation (as opposed to transfixing suture), and long mean hospital stay have also been reported to be associated with recurrent TEF. [1,3] In agreement, members of the European Reference Network for Rare Inherited Congenital Anomalies (ERNICA) put forward a consensus statement to use a transfixing suture to close the TEF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that anastomotic leakage, AS, anastomotic rupture during stricture dilatation, and indwelling esophageal foreign body increase the risk of RTEF. [3][4][5][6] RTEF may present as choking, cough or cyanosis during feeding, recurrent pneumoniae, or chronic copious production of mucus. Diagnosis of RTEF is based on symptoms, endoscopy, and radiological imaging that include computed tomography (CT) scan and supine esophageal contrast examination.…”
Section: Introductionmentioning
confidence: 99%